Efficacy of Minimal Invasive Methods in Management of Traumatic Pancreatic Injury - Bed P. Sah; Roshan Ghimire (Pancreas, 2025)
IntroductionIsolated pancreatic injury is relatively uncommon due to its mostly retroperitoneal location. However, if present, it is associated with other visceral injuries and causes serious complications if expected management is delayed.CasesIn this report we have discussed about the different minimal invasive management approaches in two cases of pancreatic injury. The first case had American Association for the Surgery of Trauma Organ Injury Scale (AAST-OIS) grade IV pancreatic injury with late presentation who underwent ultrasound-guided percutaneous drainage of pseudocyst with video assisted lavage of cavity, followed by endoscopic retrograde cholangiopancreatography (ERCP) guided pancreatic duct stenting. Second case had AAST-OIS grade II pancreatic injury which was managed with serial percutaneous drainage.ConclusionManagement of pancreatic injury is complex. Evolving trend of minimal invasive techniques of management for selected patients with higher grade pancreatic injury is associated with better outcomes.